‘Whose Gold Is This?’ The Gold of the Dutch Golden Coach - Annemarie de Wildt (Museum & Society)
This article focuses on the gold leaf of the Golden Coach, a gift from the Amsterdam population to Queen Wilhelmina in 1898, using the methodologies of object biography and object itinerary. It asks what makes the object: its final form and function, the separate parts and their materiality, or the context of users and related objects as part of a continuous process of meaning making? An exhibition at the Amsterdam Museum (2021-2022) exposed the Golden Coach's complex history along these three layers of interpretation, leading to its transformation from a national symbol to a colonial object and contributing to broader discussions of slavery and colonialism in the Netherlands. Here, the interaction between the immaterial origins of the carriage and its raw materials, such as the gold leaf, will be discussed. Advanced scientific research revealed a Surinamese origin of the gold. Why is it relevant that we know that now? And what does it mean for the future of the Golden Coach?